Honeycomb filter

By optimizing the thickness, porosity and fine pore size of the partition structure, combined with cordierite material, the problem of increasing pressure loss when the honeycomb filter is loaded is solved, and the effect of high mechanical strength and low pressure loss is achieved.

CN222173457UActive Publication Date: 2024-12-17NGK INSULATORS LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420388608.5
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Priority Date
2023-03-28
Filing Date
2024-02-29
Publication Date
2024-12-17
Estimated Expiration
2034-02-28

AI Technical Summary

Technical Problem

While the existing honeycomb filters increase porosity and thinning to reduce pressure loss, it is difficult to ensure mechanical strength, especially when loading catalysts for exhaust gas purification, the pressure loss will increase.

Method used

By optimizing the thickness, porosity, average pore diameter and base neck diameter of the partition wall, a thickness of 203 to 254 μm, a porosity of 55 to 70%, an average pore diameter of 20 to 25 μm, and a neck diameter of 11 were designed. The porous partition wall of ~18 μm, combined with cordierite as the main component material, forms a columnar honeycomb structure to ensure mechanical strength and low pressure loss.

Benefits of technology

High mechanical strength is achieved and the pressure loss increase during catalyst use is effectively suppressed, and the filtration performance of the cellular filter is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222173457U_ABST
    Figure CN222173457U_ABST
Patent Text Reader

Abstract

The utility model provides a honeycomb filter. The honeycomb filter is high in mechanical strength and can effectively restrain rising of pressure loss when a catalyst for waste gas purification is carried and used. A honeycomb filter is provided with: a columnar honeycomb structure (4) having porous partition walls (1) disposed so as to surround a plurality of cells (2) that serve as flow paths for a fluid and extend from a first end surface (11) to a second end surface (12); and a sealing part (5) which is disposed at the opening of each of the cells (2) on the first end surface (11) side or the second end surface (12) side, the thickness of the partition wall (1) being 203-254 [mu] m, the porosity of the partition wall (1) being 55-70% as measured by mercury intrusion method, the average pore diameter of the partition wall (1) being 20-25 [mu] m as measured by mercury intrusion method, and the pore diameter of the partition wall (1) being 20-25 [mu] m as measured by mercury intrusion method. The average base material neck diameter of the base material neck where the solid part of the porous base material constituting the partition wall (1) is locally thinned is 11-18 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to a honeycomb filter, and more particularly to a honeycomb filter having high mechanical strength and capable of effectively suppressing an increase in pressure loss when the honeycomb filter is used to carry a catalyst for exhaust gas purification. Background Art

[0002] In the past, a honeycomb filter using a honeycomb structure is known as a filter for capturing particulate matter in exhaust gas discharged from an internal combustion engine such as an automobile engine, and a device for purifying toxic gas components such as CO, HC, and NOx (see Patent Document 1). The honeycomb structure has a partition wall made of a porous ceramic such as cordierite, and a plurality of compartments are formed by dividing the partition wall. The honeycomb filter is provided with a sealing portion in a manner that the openings on the inlet end face side and the openings on the outlet end face side of the plurality of compartments are alternately sealed relative to the above-mentioned honeycomb structure. That is, the honeycomb filter becomes a structure in which the inlet compartments with an opening on the inlet end face side and a sealed hole on the outlet end face side and the outlet compartments with a sealed hole on the inlet end face side and an opening on the outlet end face side are alternately arranged with the partition wall. In addition, in the honeycomb filter, the porous partition wall plays the role of a filter for capturing particulate matter (such as soot) in the exhaust gas. In the following, the particulate matter contained in the exhaust gas is sometimes referred to as "PM". "PM" is the abbreviation of "particulate matter".

[0003] Various studies have been conducted to reduce the pressure loss of honeycomb filters for collecting PM in exhaust gas.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-219319 Utility Model Content

[0007] Issues to be Solved by Utility Models

[0008] As a measure for reducing the pressure loss of the honeycomb filter, various studies have been conducted on a method of increasing the porosity of the partition walls, a method of reducing the thickness of the partition walls, and the like.

[0009] However, if the porosity of the partition walls is increased in order to reduce the pressure loss of the honeycomb filter, it is difficult to ensure the material strength of the partition walls. Hereinafter, the above-mentioned "increasing the porosity of the partition walls" is sometimes referred to as "increasing the porosity of the partition walls". For example, as an example of increasing the porosity of the partition walls, when the thickness of the partition walls is set to 216 μm and the cell density is set to 46.5 cells / cm 2In the case of honeycomb filters with a porosity of 63% or less, it may be difficult to adjust the isostatic strength, which is one of the indicators of the mechanical strength of the honeycomb filter, to 1 MPa or more.

[0010] In addition, although a certain pressure loss reduction effect is obtained by thinning the thickness of the partition wall, it is difficult to ensure the material strength of the partition wall, as with the high porosity of the above-mentioned partition wall. Hereinafter, the above-mentioned "thinning the thickness of the partition wall" is sometimes referred to as "thinning the partition wall". In addition, when the high porosity and thinning of the partition wall are used together, it is more difficult to ensure the mechanical strength of the honeycomb filter, such as the isostatic strength.

[0011] The present invention has been made in view of the problems of the prior art. According to the present invention, a honeycomb filter is provided which has high mechanical strength and can effectively suppress an increase in pressure loss when used by supporting a catalyst for exhaust gas purification.

[0012] Solutions to Solve Problems

[0013] According to the present invention, a honeycomb filter shown below is provided.

[0014] [1] A honeycomb filter comprising:

[0015] A columnar honeycomb structure having porous partition walls arranged so as to surround a plurality of cells serving as a flow path of a fluid extending from a first end face to a second end face; and

[0016] a sealing portion disposed at any one of an end portion on the first end surface side and an end portion on the second end surface side of the compartment,

[0017] The thickness of the partition wall is 203 to 254 μm,

[0018] The porosity of the partition wall measured by mercury intrusion porosimetry is 55 to 70%.

[0019] The average pore diameter of the partition walls measured by mercury intrusion porosimetry is 20 to 25 μm.

[0020] The average substrate neck diameter of the substrate neck portion where the substantial portion of the porous substrate constituting the partition wall is locally narrowed is 11 to 18 μm.

[0021] [2] The honeycomb filter according to [1] above,

[0022] The pore volume ratio of pores having a pore diameter of 10 μm or less, as measured by mercury porosimetry, is 0.1 to 3.0% relative to the total pore volume of the cell walls.

[0023] [3] The honeycomb filter according to [1] or [2] above,

[0024] The cell density of the honeycomb structure is 43.4 to 49.6 cells / cm 2 .

[0025] [4] The honeycomb filter according to [1] or [2] above,

[0026] The partition walls are made of a material containing cordierite as a main component.

[0027] [5] The honeycomb filter according to [1] or [2] above,

[0028] In the pore size distribution of the cell walls measured by mercury porosimetry, the pore size D10 at which the cumulative pore volume accounts for 10% of the total pore volume is 16 to 19 μm.

[0029] Utility Model Effect

[0030] The honeycomb filter of the present invention has high mechanical strength and can effectively suppress an increase in pressure loss when used by carrying a catalyst for exhaust gas purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a perspective view schematically showing one embodiment of the honeycomb filter of the present invention, viewed from the first end surface side.

[0032] Figure 2 is from Figure 1 The honeycomb filter is shown in a top view as viewed from the first end surface side.

[0033] Figure 3 It is schematically indicated Figure 2 Cross-sectional view of the A-A' section.

[0034] In the figure:

[0035] 1—partition wall; 2—compartment; 2a—inflow compartment; 2b—outflow compartment; 3—peripheral wall; 4—honeycomb structure; 5—sealing portion; 11—first end face; 12—second end face; 100—honeycomb filter. DETAILED DESCRIPTION

[0036] The following describes the embodiments of the present invention, but the present invention is not limited to the following embodiments. Therefore, it should be understood that, within the scope of the present invention, based on the general knowledge of those skilled in the art, the following embodiments are appropriately modified, improved, etc. and fall within the scope of the present invention.

[0037] (1) Honeycomb filter:

[0038] like Figure 1 to Figure 3 As shown, one embodiment of the honeycomb filter of the utility model is a honeycomb filter 100, which includes a honeycomb structure 4 and a sealing portion 5. The honeycomb structure 4 is a columnar honeycomb structure, which has a porous partition wall 1 arranged in a manner to surround a plurality of cells 2 extending from a first end face 11 to a second end face 12, which are a flow path of a fluid. In the honeycomb filter 100, the honeycomb structure 4 is columnar, and further has an outer peripheral wall 3 on its outer peripheral side. That is, the outer peripheral wall 3 is arranged in a manner to surround the partition wall 1 arranged in a lattice shape.

[0039] Figure 1 This is a perspective view schematically showing one embodiment of the honeycomb filter of the present invention, viewed from the first end surface side (for example, the inlet end surface side). Figure 2 is from Figure 1 The honeycomb filter is shown in a top view as viewed from the first end face side (eg, the inlet end face side). Figure 3 It is schematically indicated Figure 2 Cross-sectional view of the A-A' section.

[0040] The honeycomb filter 100 has a particularly important characteristic in the structure of the partition wall 1 constituting the honeycomb structure 4. That is, the partition wall 1 constituting the honeycomb structure 4 has a thickness of 203 to 254 μm. In addition, the porosity of the partition wall 1 measured by the mercury intrusion method is 55 to 70%, and the average pore diameter of the partition wall 1 measured by the mercury intrusion method is 20 to 25 μm. Furthermore, in the partition wall 1, the average substrate neck diameter of the substrate neck where the solid part of the porous substrate constituting the partition wall 1 is locally narrowed is 11 to 18 μm. The honeycomb filter 100 thus constructed has high mechanical strength and can effectively suppress the increase in pressure loss when used while carrying a catalyst for exhaust gas purification. In particular, in the honeycomb filter 100 of the present embodiment, the thickness of the partition wall 1 is 203 to 254 μm, the porosity of the partition wall 1 is 55 to 70%, and the porous partition wall 1 can achieve excellent mechanical strength despite having a high porosity and a thin wall. As a reason for this, it can be cited that the average pore diameter of the partition wall 1 is 20 to 25 μm, and the average substrate neck diameter of the above-mentioned substrate neck is 11 to 18 μm. That is, the partition wall 1 in the honeycomb filter 100 of the present embodiment is configured such that the substrate neck in the porous substrate constituting the partition wall 1 is thicker than the substrate neck in the previous porous substrate, and the average substrate neck diameter of the porous substrate is 11 to 18 μm. Therefore, the material strength of the porous substrate constituting the partition wall 1 is high, and excellent mechanical strength (for example, isostatic strength) can be achieved. Below, the partition wall 1 constituting the honeycomb structure 4 is described in more detail.

[0041] The thickness of the partition wall 1 is 203 to 254 μm. If other structures other than the thickness of the partition wall 1 are satisfied (for example, the numerical ranges of the above-mentioned porosity, average pore size, etc.), and the thickness of the partition wall 1 is less than 203 μm, the mechanical strength of the partition wall 1 is reduced. On the other hand, if the thickness of the partition wall 1 exceeds 254 μm, when the partition wall 1 carries a catalyst for exhaust gas purification, the pressure loss of the honeycomb filter 100 sometimes increases. The thickness of the partition wall 1 may be 203 to 254 μm, for example, preferably 216 to 241 μm, and more preferably 224 to 236 μm. The thickness of the partition wall 1 can be measured, for example, using a scanning electron microscope or a microscope.

[0042] The porosity of the partition wall 1 is 55 to 70%. The porosity of the partition wall 1 is a value measured by mercury intrusion. The porosity of the partition wall 1 can be measured, for example, using Autopore 9500 (trade name) manufactured by Micromeritics. The porosity can be measured by cutting out a portion of the partition wall 1 from the honeycomb filter 100 as a test piece and using the test piece obtained in this way. If the porosity of the partition wall 1 is less than 55%, the pressure loss of the honeycomb filter 100 sometimes increases when the partition wall 1 carries a catalyst for exhaust gas purification. In addition, if the porosity of the partition wall 1 exceeds 70%, the mechanical strength of the honeycomb filter 100 sometimes decreases. The porosity of the partition wall 1 may be 55 to 70%, for example, preferably 58 to 67%, and more preferably 60 to 65%.

[0043] The average pore diameter of the partition wall 1 is 20 to 25 μm. The average pore diameter of the partition wall 1 is a value measured by mercury intrusion. The average pore diameter of the partition wall 1 can be measured, for example, using Autopore 9500 (trade name) manufactured by Micromeritics. The average pore diameter can be measured using a test piece used in the above-mentioned porosity measurement. If the average pore diameter of the partition wall 1 is less than 20 μm, the pressure loss of the honeycomb filter 100 sometimes increases when the partition wall 1 carries a catalyst for exhaust gas purification. In addition, if the average pore diameter of the partition wall 1 exceeds 25 μm, the collection efficiency of the honeycomb filter 100 sometimes decreases. The average pore diameter of the partition wall 1 may be 20 to 25 μm, for example, preferably 23 to 25 μm, and more preferably 24 to 25 μm.

[0044] Furthermore, in the partition wall 1 of the honeycomb filter 100 of the present embodiment, the average substrate neck diameter of the substrate neck where the solid part of the porous substrate constituting the partition wall 1 is locally thinned is 11 to 18 μm. By satisfying the porosity, average pore diameter and other configurations of the partition wall 1 described above, and setting the average substrate neck diameter of the substrate neck to 11 to 18 μm, the number of small pores constituting the porous substrate of the partition wall 1 is reduced, and the substrate neck diameter of the porous substrate is thickened. Therefore, the honeycomb filter 100 of the present embodiment can suppress the reduction of mechanical strength, and can effectively suppress the increase of pressure loss of the honeycomb filter 100, especially when the partition wall 1 carries a catalyst for exhaust gas purification.

[0045] The average substrate neck diameter of the substrate neck may be 11 to 18 μm, for example, preferably 13 to 18 μm, and more preferably 15 to 18 μm. In addition, if the average substrate neck diameter is less than 11 μm, the mechanical strength may sometimes be reduced while satisfying other structures related to the partition wall 1 such as the porosity and the average pore diameter. In addition, if it is desired to improve the mechanical strength by adjusting other structures such as the porosity and the average pore diameter, the pressure loss of the honeycomb filter 100 may sometimes be increased when the partition wall 1 carries a catalyst for exhaust gas purification. On the other hand, if the average substrate neck diameter exceeds 18 μm, the average pore diameter may sometimes become relatively large, and the collection efficiency of the honeycomb filter 100 may become low.

[0046] The average substrate neck diameter of the substrate neck of the porous substrate constituting the next door 1 can be measured as follows. First, the porous body data of the porous substrate constituting the next door 1 is obtained based on three-dimensional scanning. The device for three-dimensional scanning can be, for example, Xradia 520Versa (trade name) manufactured by Zeiss. The resolution of each direction of X, Y, and Z is 1.2 μm, respectively, and the cube with a side of 1.2 μm obtained thereby becomes a voxel. The data obtained by three-dimensional CT scanning is, for example, brightness data of each coordinate of X, Y, and Z. Such brightness data is binarized using a predetermined threshold value and whether it is a space voxel or an object voxel is determined for each coordinate, thereby obtaining three-dimensional porous body data (hereinafter also referred to as "porous body three-dimensional data"). The threshold value is determined, for example, by Otsu's binarization based on the brightness distribution of the brightness data. For example, there is no particular restriction on the range of obtaining the porous body data of the next door 1. The range for obtaining the porous body data of the partition wall 1 can be appropriately determined according to an apparatus for three-dimensional scanning, and an example thereof is 480 μm×480 μm×thickness (μm) of the partition wall 1 .

[0047] Next, the obtained three-dimensional porous body data was segmented at the constricted portion by the WaterShed method. The SNOW algorithm was installed in the program, and segmentation by the WaterShed method was performed.

[0048] In addition, regarding the divided substrates formed by dividing the substrate at the necking portion, the "aggregate of voxels" between one divided substrate and the other divided substrates adjacent to the one divided substrate is regarded as the "substrate neck" that separates the substrates from each other. The value obtained by multiplying the number of voxels constituting the substrate neck by the square of the grid resolution (1.2 μm) (i.e., the number of voxels × (1.2 μm) 2 ) as the substrate neck area. The average substrate neck diameter is Find out.

[0049] Preferably, the pore volume ratio of the pores with a pore diameter of 10 μm or less measured by mercury intrusion in the partition wall 1 is 0.1 to 3.0% relative to the total pore volume of the partition wall 1. Thus, in the honeycomb filter 100 of the present embodiment, the porous substrate constituting the partition wall 1 preferably has a small pore volume ratio of pores with a pore diameter of 10 μm or less (small pores) with a relatively small pore diameter. The actual lower limit of the pore volume ratio of pores with a pore diameter of 10 μm or less is 0.1% as mentioned above. If the pore volume ratio of pores with a pore diameter of 10 μm or less exceeds 3.0%, as the small pores increase, the average substrate neck diameter of the substrate neck is difficult to become thicker. Therefore, it is sometimes difficult to control the average substrate neck diameter of the substrate neck within the range of 11 to 18 μm. The pore volume ratio of the pores with a pore diameter of 10 μm or less relative to the total pore volume of the partition wall 1 can be measured using the same measuring method as the porosity and average pore diameter of the partition wall 1, such as Autopore 9500 (trade name) made by Micromeritics. In addition, without particular limitation, the pore volume ratio of the pores with a pore diameter of 10 μm or less relative to the total pore volume of the partition wall 1 is, for example, more preferably 0.1 to 2.0%.

[0050] Furthermore, for the partition wall 1 in the honeycomb filter 100 of the present embodiment, in the pore size distribution of the partition wall 1 measured by the mercury intrusion method, the pore size D10 at which the cumulative pore volume is 10% of the total pore volume is preferably 16 to 19 μm. Hereinafter, the above-mentioned "value of the pore size D10 at which the cumulative pore volume is 10% of the total pore volume" is sometimes referred to as the "value of D10" in the pore size distribution of the partition wall 1. The value of D10 in the above-mentioned pore size distribution of the honeycomb filter 100 of the present embodiment is preferably set to a high value such as 16 to 19 μm. By setting the value of D10 in the pore size distribution to be high and reducing small pores, the permeation resistance of the partition wall 1 is reduced, and the increase in the pressure loss of the honeycomb filter 100 can be effectively suppressed. The value of D10 in the pore size distribution is, for example, more preferably 18 to 19 μm.

[0051] The cumulative pore volume of the partition wall 1 is a value measured by the mercury intrusion method as described above. The measurement of the cumulative pore volume of the partition wall 1 can be carried out, for example, using Autopore 9500 (trade name) manufactured by Micromeritics. The measurement of the cumulative pore volume of the partition wall 1 can be carried out by the following method. First, a portion of the partition wall 1 is cut out from the honeycomb filter 100 to prepare a test piece for the cumulative pore volume measurement. There is no particular restriction on the size of the test piece, for example, it is preferably a rectangular parallelepiped with a length of about 10 mm, about 10 mm, and about 20 mm in length, width, and height, respectively. There is no particular restriction on the location of the partition wall 1 from which the test piece is cut out, and the test piece is preferably cut out near the axial center of the honeycomb structure 4 of the honeycomb filter 100 and made. The obtained test piece is placed in the measuring compartment of the measuring device, and the interior of the measuring compartment is depressurized. Next, mercury is introduced into the measuring compartment. Next, the mercury introduced into the measuring compartment is pressurized, and when pressurized, the volume of mercury pressed into the pores present in the test piece is measured. At this time, as the pressure applied to the mercury increases, the mercury is pressed into the pores with smaller pore diameters from the pores with larger pore diameters in sequence. Therefore, based on the relationship between the "pressure applied to the mercury" and the "volume of mercury pressed into the pores", the relationship between the "pore diameter of the pores formed in the test piece" and the "cumulative pore volume" can be obtained. To explain in more detail, as described above, by the mercury intrusion method, when pressure is gradually applied in order to make mercury penetrate into the pores of the sample (test piece) in a container sealed in a vacuum state, the mercury to which pressure is applied penetrates from the large pores to the small pores of the sample in sequence. Based on the pressure at this time and the amount of mercury pressed in, the pore diameter of the pores formed in the sample and its pore volume can be calculated. In the following, when the pore diameter is set to a1, a2, a3..., the relationship a1>a2>a3... is satisfied. Among them, the average pore diameter between each measurement point (for example, a1 to a2) can be expressed on the horizontal axis as "average pore diameter = (a1+a2) / 2". The Log differential pore volume on the vertical axis can be a value obtained by dividing the increase in pore volume dV between the measurement points by the logarithmic difference of the pore diameter (ie, "log(a1)-log(a2)").

[0052] There is no particular restriction on the shape of the compartment 2 formed in the honeycomb structure 4. For example, as the shape of the compartment 2 in the cross section orthogonal to the direction in which the compartment 2 extends, polygons, circles, ellipses, etc. can be cited. As polygons, triangles, quadrilaterals, pentagons, hexagons, octagons, etc. can be cited. In addition, the shape of the compartment 2 is preferably a triangle, a quadrilateral, a pentagon, a hexagon, an octagon. In addition, with respect to the shape of the compartment 2, the shapes of all compartments 2 can be the same shape or different shapes. For example, although the illustration is omitted, it can also be a compartment in which quadrilateral compartments and octagonal compartments are mixed. In addition, with respect to the size of the compartment 2, the size of all compartments 2 can be the same or different. For example, although the illustration is omitted, the size of a part of the compartments in the plurality of compartments can also be increased, and the size of other compartments can be relatively reduced. In addition, in the utility model, the compartment 2 refers to the space surrounded by the next door 1.

[0053] The cell density of the cells 2 formed by partitioning the cells 1 is preferably 43.4 to 49.6 cells / cm 2 , more preferably 45.0 to 48.1 pieces / cm 2 With such a configuration, the honeycomb filter 100 can be suitably used as a filter for purifying exhaust gas exhausted from an engine of a vehicle.

[0054] The partition wall 1 is preferably composed of a porous material of ceramic, and in particular, more preferably a material comprising cordierite as a main component. That is, the partition wall 1 is more preferably a porous substrate composed of a material comprising cordierite as a main component. Wherein, "main component" refers to a component having more than 90 mass % in the component. The material constituting the partition wall 1 preferably comprises more than 92 mass % of cordierite, and more preferably comprises more than 94 mass %. Moreover, the partition wall 1 is particularly preferably composed of cordierite except for the components inevitably contained.

[0055] The peripheral wall 3 of the honeycomb structure 4 may be formed integrally with the partition wall 1, or may be a peripheral coating formed by coating a peripheral coating material on the peripheral side of the partition wall 1. For example, although not shown in the figure, the peripheral coating may be formed integrally with the partition wall and the peripheral wall during manufacture, and then the peripheral wall formed may be removed by a known method such as grinding, and then provided on the peripheral side of the partition wall.

[0056] There is no particular limitation on the shape of the honeycomb structure 4. Examples of the shape of the honeycomb structure 4 include a first end face 11 (eg, inflow end face) and a second end face 12 (eg, outflow end face) that are circular, elliptical, polygonal, or other cylindrical shapes.

[0057] There is no particular limitation on the size of the honeycomb structure 4, such as the length from the first end face 11 to the second end face 12, and the size of the cross section of the honeycomb structure 4 perpendicular to the direction in which the cells 2 extend. When the honeycomb filter 100 is used as a filter for purifying exhaust gas, each size can be appropriately selected in order to obtain the best purification performance.

[0058] In the honeycomb filter 100, a sealing portion 5 is provided at the opening on the first end face 11 side of a predetermined cell 2 and at the opening on the second end face 12 side of the remaining cells 2. In the case where the first end face 11 is set as the inlet end face and the second end face 12 is set as the outlet end face, the cell 2 having the sealing portion 5 provided at the opening on the outlet end face side and the inlet end face side opening is set as the inlet cell 2a. In addition, the cell 2 having the sealing portion 5 provided at the opening on the inlet end face side and the outflow end face side opening is set as the outflow cell 2b. The inlet cells 2a and the outflow cells 2b are preferably alternately provided across the partition wall 1. Moreover, it is preferred that a checkered pattern is formed on both end faces of the honeycomb filter 100 using the sealing portion 5 and the "opening of the cell 2".

[0059] The material of the plugging portion 5 is not particularly limited and may be, for example, the same material as that of the partition walls 1 described above or a material different from that of the partition walls 1 .

[0060] The honeycomb filter 100 preferably carries a catalyst for exhaust gas purification on the partition wall 1 that divides the plurality of cells 2. Carrying the catalyst on the partition wall 1 means coating the catalyst on the surface of the partition wall 1 and the inner wall of the pores formed in the partition wall 1. By configuring in this way, CO, NOx, HC, etc. in the exhaust gas can be made harmless by catalytic reaction. In addition, the oxidation of PM such as coal captured can be promoted.

[0061] There is no particular limitation on the catalyst supported on the partition wall 1. For example, as such a catalyst, a catalyst containing a platinum group element, that is, a catalyst containing an oxide of at least one element of aluminum, zirconium and cerium can be cited. The supported amount of the catalyst is preferably 50 to 100 g / L. In addition, the supported amount of the catalyst (g / L) in this specification represents the amount (g) of the catalyst supported per unit volume (L) of the honeycomb filter 100.

[0062] (2) Method for manufacturing honeycomb filter:

[0063] for Figure 1 to Figure 3The manufacturing method of the honeycomb filter of the present embodiment shown is not particularly limited, and can be manufactured, for example, by the following method. First, plastic clay for making a honeycomb structure is prepared. The clay for making a honeycomb structure can be prepared, for example, as follows. Talc, alumina, aluminum hydroxide, silicon dioxide, etc. can be used as raw material powders, and these raw material powders are prepared into a chemical composition in which silicon dioxide is in the range of 42 to 56 mass%, aluminum oxide is in the range of 30 to 45 mass%, and magnesium oxide is in the range of 12 to 16 mass%.

[0064] In the honeycomb filter of the present embodiment, the average substrate neck diameter of the substrate neck of the porous substrate constituting the partition wall is 11 to 18 μm. As a method for manufacturing such a honeycomb filter, for example, in the preparation of green clay, it is preferred to prepare the green clay without using kaolin, which has been used as a raw material powder for green clay in the past. In particular, kaolin generally has a small raw material particle size. By using green clay prepared using a raw material powder that does not contain such kaolin with a small raw material particle size, the average substrate neck diameter of the substrate neck can be made coarser than that of the porous substrate manufactured by the previous manufacturing method. For example, talc with a particle size of 15 to 25 μm, alumina with a particle size of 4 to 8 μm, etc. can be used as raw materials.

[0065] Next, the kneaded clay obtained in this manner is extruded to produce a honeycomb molded body having partition walls for partitioning and forming a plurality of cells and an outer peripheral wall disposed so as to surround the partition walls.

[0066] The obtained honeycomb formed body is dried by microwaves and hot air, for example, and the openings of the cells are sealed with the same material as that used for manufacturing the honeycomb formed body, thereby manufacturing the sealed portions. After manufacturing the sealed portions, the honeycomb formed body may be further dried.

[0067] Next, the honeycomb formed body with the plugged portions is fired to produce a honeycomb filter. The firing temperature and firing atmosphere vary depending on the raw material, and a person skilled in the art can select the firing temperature and firing atmosphere most suitable for the selected material.

[0068] [Example]

[0069] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.

[0070] (Example 1)

[0071] 3.4 parts by mass of pore-forming material, 1.0 parts by mass of dispersion medium and 6.0 parts by mass of organic binder were added to 100 parts by mass of cordierite raw material, mixed and kneaded to prepare green clay. Methylcellulose was used as an organic binder. Potassium laurate soap was used as a dispersant. A water-absorbent polymer with an average particle size of 30 μm was used as a pore-forming material. Talc, alumina, silica gel and aluminum hydroxide were used as cordierite raw materials.

[0072] Next, the obtained clay is formed using an extruder to produce a honeycomb formed body. Next, the obtained honeycomb formed body is dried by high-frequency induction heating and further dried using a hot air dryer. The shape of the cells in the honeycomb formed body is a quadrilateral.

[0073] Next, a sealing portion is formed on the dried honeycomb formed body. First, a mask is applied to the inlet end face of the honeycomb formed body. Next, the end to which the mask is applied (the end on the inlet end face side) is immersed in the sealing slurry, and the opening of the cell to which the mask is not applied (the outflow cell) is filled with the sealing slurry. In this way, a sealing portion is formed on the inlet end face side of the honeycomb formed body. Then, a sealing portion is also formed in the inlet cell of the outflow end face of the dried honeycomb formed body.

[0074] Next, the honeycomb formed body with the sealed portion formed was dried using a microwave dryer, and after being completely dried using a hot air dryer, both end faces of the honeycomb formed body were cut and adjusted to a predetermined size. Next, the dried honeycomb formed body was degreased and sintered to manufacture the honeycomb filter of Example 1.

[0075] The diameter of the end surface of the honeycomb filter of Example 1 was 118.4 mm, and the length in the cell extending direction was 152.4 mm. In addition, the thickness of the partition wall was 203.2 μm, and the cell density was 41.9 cells / cm 2 .

[0076] For the honeycomb filter of Example 1, the porosity (%) and average pore diameter (μm) of the partition wall are measured by the following method. In addition, the pore diameter distribution of the partition wall is determined using the device used in the determination of the porosity and average pore diameter shown below. Based on the pore diameter distribution obtained, the pore volume ratio (%) of pores with a pore diameter of 10 μm or less relative to the total pore volume and the value (μm) of the pore diameter D10 with a cumulative pore volume of 10% of the total pore volume are determined. In addition, the average substrate neck diameter (μm) of the substrate neck of the porous substrate constituting the partition wall is determined by the following method. The results are shown in Table 1.

[0077] [Table 1]

[0078]

[0079] [Porosity (%) and average pore size (μm)]

[0080] The porosity and average pore size of the partition wall were measured using Autopore 9500 (trade name) manufactured by Micromeritics. In the determination of porosity and average pore size, a portion of the partition wall was cut out from the honeycomb filter as a test piece, and the obtained test piece was used to measure the porosity. The test piece was a rectangular parallelepiped having a length of about 10 mm, about 10 mm, and about 20 mm in length, width, and height, respectively. The collection site of the test piece was set near the center of the axial direction of the honeycomb filter.

[0081] [Average substrate neck diameter (μm)]

[0082] First, the three-dimensional data of the porous body of the next door is measured by three-dimensional scanning. The three-dimensional scanning uses Xradia 520Versa (trade name) manufactured by Zeiss. The resolution of the three-dimensional data of the porous body in the X, Y, and Z directions is 1.2 μm, respectively, and the resulting cube with a side of 1.2 μm is called a voxel. The three-dimensional data of the porous body is the brightness data of each coordinate of X, Y, and Z. Next, for the three-dimensional data of the porous body, the substrate is divided at the necking part by the WaterShed method. The SNOW algorithm is installed in the program to implement the above-mentioned division of the WaterShed method. For the divided substrate formed by dividing the substrate as described above, the collection of voxels between two adjacent divided substrates is regarded as the substrate neck. The value obtained by multiplying the number of voxels constituting such a substrate neck by the square of the grid resolution (1.2 μm) (i.e., the number of voxels × (1.2 μm) 2 ) as the substrate neck area, using Calculate the average substrate neck diameter.

[0083] The honeycomb filter of Example 1 was evaluated for A-axis compressive strength and pressure loss by the following method. In addition, in each evaluation of A-axis compressive strength and pressure loss, a catalyst containing a platinum group element was loaded on each honeycomb filter to be evaluated by the following method, and the measurements were performed after the catalyst was loaded. The results are shown in Table 2.

[0084] [Table 2]

[0085]

[0086] [Method of supporting catalyst]

[0087] First, a catalyst slurry containing aluminum oxide with an average particle size of 30 μm is prepared. Then, the catalyst is loaded on the honeycomb filter using the prepared catalyst slurry. Specifically, the catalyst is loaded by dipping the honeycomb filter, and then the excess catalyst slurry is blown away by air, thereby loading a predetermined amount of catalyst on the partition wall of the honeycomb filter. Then, the honeycomb filter loaded with the catalyst is dried at a temperature of 100°C, and further heat-treated at 500°C for 2 hours to obtain a honeycomb filter with a catalyst. The loading amount of the catalyst loaded on the honeycomb filter of Example 1 is 75 g / L.

[0088] [A-axis compression strength]

[0089] A test piece of about 25.4 mm in diameter and 25.4 mm in length cut from the product (honeycomb filter) is used as a specimen, and a load is continuously applied at a head speed of the testing machine of less than 1 mm / min. The load F at the time of destruction is read, and the compressive strength P is calculated by the following formula (1), and the A-axis compressive strength (MPa) of the honeycomb filter is determined. The "A-axis compressive strength ratio" column in Table 2 shows the values ​​(%) of the A-axis compressive strength of each embodiment and the honeycomb filter with catalyst of the comparative example when the value of the A-axis compressive strength of the honeycomb filter with catalyst of the comparative example 1 is set to 100%. In the evaluation of the A-axis compressive strength, the honeycomb filter of each embodiment is evaluated based on the following evaluation criteria.

[0090] P=F / S (1)

[0091] (In the above formula (1), P represents the compressive strength (Pa), F represents the load at failure (N), and S represents the cross-sectional area of ​​the sample (m 2 ). In addition, the sample cross-sectional area S is 5.067×10 -4 m 2 .

[0092] Evaluation "excellent": When the value of the A-axis compressive strength ratio (%) is 150% or more, this evaluation is set to "excellent".

[0093] Evaluation "good": When the value of the A-axis compressive strength ratio (%) was 120% or more and less than 150%, this evaluation was set to "good".

[0094] Evaluation "acceptable": When the value of the A-axis compressive strength ratio (%) is 100% or more and less than 120%, this evaluation is regarded as "acceptable".

[0095] Evaluation "failure": When the value of the A-axis compressive strength ratio (%) is less than 100%, this evaluation is regarded as "failure".

[0096] [Pressure loss]

[0097] The exhaust gas from a 1.2L direct injection gasoline engine was heated to 700°C and 600m 3 / h flow rate flows in, and the pressures on the inlet end face side and the outlet end face side of the honeycomb filter with catalyst are measured. Then, the pressure loss (kPa) of the honeycomb filter is determined by calculating the pressure difference between the inlet end face side and the outlet end face side. The "Pressure Loss Ratio" column of Table 2 shows the pressure loss values ​​(%) of each embodiment and the honeycomb filter with catalyst of the comparative example when the pressure loss value of the honeycomb filter with catalyst of the comparative example 1 is set to 100%. In the pressure loss evaluation, the honeycomb filter of each embodiment is evaluated based on the following evaluation criteria.

[0098] Evaluation "excellent": When the value of the pressure loss ratio (%) was 80% or less, the evaluation was set to "excellent".

[0099] Evaluation "good": When the value of the pressure loss ratio (%) was more than 80% and not more than 90%, the evaluation was set to "good".

[0100] Evaluation "acceptable": When the value of the pressure loss ratio (%) was more than 90% and not more than 100%, the evaluation was set as "acceptable".

[0101] Evaluation "failure": When the value of the pressure loss ratio (%) exceeded 100%, the evaluation was set as "failure".

[0102] (Examples 2 to 8)

[0103] In Examples 2 to 8, in the preparation of green clay for making a honeycomb formed body, a honeycomb filter was manufactured using the raw materials shown below. For the obtained honeycomb filter, the porosity of the partition wall and the average pore diameter were measured by the same method as in Example 1. In addition, in the above method, the pore volume ratio (%) of pores below 10 μm, the value of D10 (μm), and the average substrate neck diameter (μm) were calculated. The results are shown in Table 1. In Examples 2 to 8, a raw material powder that does not contain kaolin was used in the raw material powder used to prepare green clay.

[0104] (Comparative Examples 1 to 7)

[0105] In Comparative Examples 1 to 7, in the preparation of green clay for making honeycomb formed bodies, honeycomb filters were manufactured using the raw materials shown below. For the obtained honeycomb filter, the porosity of the partition wall and the average pore size were measured by the same method as in Example 1. In addition, in the above method, the pore volume ratio (%) of pores below 10 μm, the value of D10 (μm), and the average substrate neck diameter (μm) were calculated. The results are shown in Table 1. In Comparative Examples 1 and 2, a raw material powder containing kaolin was used in the raw material powder used to prepare green clay. In Comparative Examples 3 to 7, a raw material powder not containing kaolin was used in the raw material powder used to prepare green clay, and the particle size of the raw material powder or the particle size of the pore-forming material was adjusted so that the porosity of the partition wall and the average pore size became the values ​​of Table 1.

[0106] The honeycomb filters of Examples 2 to 8 and Comparative Examples 1 to 7 were evaluated for A-axis compressive strength and pressure loss by the same method as in Example 1. Table 2 shows the results.

[0107] (result)

[0108] The honeycomb filters of Examples 1 to 8 showed superior results in the evaluation of A-axis compressive strength and pressure loss compared to the honeycomb filter of Comparative Example 1, which was used as the evaluation standard. In particular, the honeycomb filter of Example 1 had a base neck diameter of 15 μm, and the evaluation results of A-axis compressive strength were particularly excellent. In addition, the honeycomb filter of Example 6 had a base neck diameter of 16 μm, and the evaluation results of A-axis compressive strength were also particularly excellent. The honeycomb filter of Example 7 had a pore volume fraction of pores less than 10 μm of 2.5%, and the evaluation results of pressure loss were particularly excellent.

[0109] On the other hand, the honeycomb filter of Comparative Example 2 had an average substrate neck diameter of 10 μm and a porosity of 65%, and the evaluation result of the A-axis compressive strength was inferior to that of the honeycomb filter of Comparative Example 1, which was used as the evaluation standard. The honeycomb filter of Comparative Example 3 had an average pore diameter of 17 μm, and the evaluation result of the pressure loss after catalyst loading (hereinafter, also referred to as catalyst coating) was inferior to that of the honeycomb filter of Comparative Example 1, which was used as the evaluation standard. The honeycomb filter of Comparative Example 4 had a porosity of 71%, and the evaluation result of the A-axis compressive strength was inferior to that of the honeycomb filter of Comparative Example 1, which was used as the evaluation standard. The honeycomb filter of Comparative Example 5 had a porosity of 54%, and the evaluation result of the pressure loss after catalyst coating was inferior to that of the honeycomb filter of Comparative Example 1, which was used as the evaluation standard. The partition wall thickness of the honeycomb filter of Comparative Example 6 was 266.7 μm, and the evaluation result of the pressure loss after catalyst coating was inferior to that of the honeycomb filter of Comparative Example 1, which was used as the evaluation standard. The partition wall thickness of the honeycomb filter of Comparative Example 7 was 190.5 μm, and the evaluation result of the A-axis compressive strength was inferior to that of the honeycomb filter of Comparative Example 1, which was used as the evaluation standard.

[0110] Possibility of Industrial Application

[0111] The honeycomb filter of the present invention can be used as a collection filter for removing particulates and the like contained in exhaust gas.

Claims

1. A honeycomb filter, characterized in that: have: A columnar honeycomb structure having porous partition walls arranged so as to surround a plurality of cells serving as a flow path for a fluid extending from a first end face to a second end face; as well as a sealing portion disposed at any one of an end portion on the first end surface side and an end portion on the second end surface side of the compartment, The thickness of the partition wall is 203 to 254 μm, The porosity of the partition wall measured by mercury intrusion porosimetry is 55 to 70%. The average pore diameter of the partition walls measured by mercury intrusion porosimetry is 20 to 25 μm. The average substrate neck diameter of the substrate neck portion where the substantial portion of the porous substrate constituting the partition wall is locally narrowed is 11 to 18 μm.

2. The honeycomb filter according to claim 1, characterized in that The pore volume ratio of pores having a pore diameter of 10 μm or less, as measured by mercury porosimetry, is 0.1 to 3.0% relative to the total pore volume of the cell walls.

3. The honeycomb filter according to claim 1 or 2, characterized in that: The cell density of the honeycomb structure is 43.4 to 49.6 cells / cm 2 .

4. The honeycomb filter according to claim 1 or 2, characterized in that: The partition walls are made of a material containing cordierite as a main component.

5. The honeycomb filter according to claim 1 or 2, characterized in that: In the pore size distribution of the cell walls measured by mercury porosimetry, the pore size D10 at which the cumulative pore volume accounts for 10% of the total pore volume is 16 to 19 μm.